DNA methylation dynamics during B cell maturation underlie a continuum of disease phenotypes in chronic lymphocytic leukemia - Oakes, Christopher C; Seifert, Marc; Assenov, Yassen; Gu, Lei; Przekopowitz, Martina; Ruppert, Amy S; Wang, Qi; Imbusch, Charles D; Serva, Andrius; Koser, Sandra D; Brocks, David; Lipka, Daniel B; et al. (Nature genetics, 2016)
Christoph Plass, Christopher Oakes and colleagues study genome-wide DNA methylation dynamics during B cell maturation and the pathogenic role of transcription factor dysregulation in chronic lymphocytic leukemia (CLL). By comparing normal and malignant B cells, they find that tumors derive from a continuum of maturation states, which correlate with different clinical outcomes. Charting differences between tumors and normal tissue is a mainstay of cancer research. However, clonal tumor expansion from complex normal tissue architectures potentially obscures cancer-specific events, including divergent epigenetic patterns. Using whole-genome bisulfite sequencing of normal B cell subsets, we observed broad epigenetic programming of selective transcription factor binding sites coincident with the degree of B cell maturation. By comparing normal B cells to malignant B cells from 268 patients with chronic lymphocytic leukemia (CLL), we showed that tumors derive largely from a continuum of maturation states reflected in normal developmental stages. Epigenetic maturation in CLL was associated with an indolent gene expression pattern and increasingly favorable clinical outcomes. We further uncovered that most previously reported tumor-specific methylation events are normally present in non-malignant B cells. Instead, we identified a potential pathogenic role for transcription factor dysregulation in CLL, where excess programming by EGR and NFAT with reduced EBF and AP-1 programming imbalances the normal B cell epigenetic program.